Literature Review: Environmental and Cultural Preservation in the Indigenous Village of Kasepuhan Ciptagelar, Bandung Regency, West Java, as a Symbol of Traditional Community Compliance - Sidik, Abdul Faqih Fajar; Surtikanti, Hertien Koosbandiah (-, 2025)
Indonesia has more than 300 ethnic groups, of which the Javanese are the most widely distributed. The province of West Java displays a variety of cultures and traditions, such as the Ciptagelar indigenous community, which, although they feel they are part of Banten, maintains its cultural distinctiveness. Local wisdom plays an important role in maintaining culture, is passed down from generation to generation and reflects the values that influence community life. The Kasepuhan Ciptagelar traditional community inherits and upholds the wisdom of their ancestors, passing it on orally from generation to generation. The traditional rules of ancestral heritage, known as tatali paranti karuhun, are the main guide in the life and outlook of the Ciptagelar community. This wisdom is based on the advice of their parents. and ideas from elders, guiding them in preserving culture and the environment with full dedication. Their adherence to customs and traditions strengthens their commitment to preserving nature, reflected in the wise use of natural resources and maintaining the balance of the local ecosystem.